Manajemen Laba Dalam Praktik Manajemen Impresi Pada Perusahaan Bumn Yang Terdaftar Di Bei Periode 2012-2014 - Zain, Amanta (AKRUAL: JURNAL AKUNTANSI, 2015)
AbstractThis study aimed to examine the effect of earnings management on impression management in the Management Discussion and Analysis (MD&A) that is focused on the financial performance analysis. Earnings management is measured using discretionary accruals and impression management is measured using an index that includes self-serving attribution and accounting explanation bias. This study uses the firmâs size and liquidity ratio (current ratio) as control variables that are considered relevant and have interaction with the independent variables and the dependent variable was tested in this study. Samples were obtained from annual reports of state-owned enterprises listed on the Indonesia Stock Exchange during the period 2012 to 2014. The results showed that earnings management does not have a significant influence on the management of state-owned enterprises impression. However, the control variables firmâs size and liquidity ratio (current ratio) was shown to significantly affect the management of state-owned enterprises impression.